Conventional exercises plan with or without laser guided feedback for patients with non-specific low back pain - Khan, Muhammad Basit; Rana, Arif Ali; Hira Rehman; Akram, Nishat (Medical Journal of South Punjab, 2024)
Objective: To find out what changes occurred after the application of two exercise modalities conventional Exercise and Laser-Guided Exercise on pain, pain pressure thresholds, disability, catastrophizing, kinesiophobia, and lumbar proprioception in subjects with nonspecific chronic low back pain (NSCLBP). Methodology: The study employed a randomized clinical trial design, conducted at Gillani Physiotherapy and Medical Center, Lahore. The inclusion criteria include participants who are between 18-45 years with non-specific low back pain and volunteer convenient sampling technique was used. Group A received conventional physical therapy program and group B received conventional physical therapy exercise program along with laser therapy which consists of infrared radiation therapy. Measurement instruments used in data collection were based on Numeric Pain Rating Scale and Oswestry Disability Index. Data analysis was done using statistical packages for social sciences (SPSS) version 25, and statistical analysis techniques used were Shapiro–Wilk test, Wilcoxon signed rank test and Mann–Whitney U test. Results: The study involved 30 participants with non-specific low back pain. The mean age was 34.93±7.93 SD years, with 43.3% males and 56.7% females. Mann-Whitney U tests showed no significant differences in pre-intervention scores but significant post-intervention improvements in Group Oswestry Disability Index (p = 0.016). Wilcoxon signed-rank tests revealed significant improvements in both disability and pain levels for both groups post-treatment (p < 0.001), with Group B showing more substantial improvements (Oswestry p < 0.001; Pain p < 0.001). Conclusion: Current study concluded that both conventional physical therapy combined with laser therapy significantly improve disability and pain level in patients with non-specific low back pain.